Assessing temporal trends and source regions of per- and polyfluoroalkyl substances (PFASs) in air under the Arctic Monitoring and Assessment Programme (AMAP). (January 2018) - Wong, Fiona; Shoeib, Mahiba; Katsoyiannis, Athanasios; Eckhardt, Sabine; Stohl, Andreas; Bohlin-Nizzetto, Pernilla; Li, Henrik; Fellin, Phil; Su, Yushan; Hung, Hayley
Abstract: Long-term Arctic air monitoring of per- and polyfluoroalkyl substances (PFASs) is essential in assessing their long-range transport and for evaluating the effectiveness of chemical control initiatives. We report for the first time temporal trends of neutral and ionic PFASs in air from three arctic stations: Alert (Canada, 2006–2014); Zeppelin (Svalbard, Norway, 2006–2014) and Andøya (Norway, 2010–2014). The most abundant PFASs were the perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorobutanoic acid (PFBA), and fluorotelomer alcohols (FTOHs). All of these chemicals exhibited increasing trends at Alert with doubling times ( t 2 ) of 3.7 years (y) for PFOA, 2.9 y for PFOS, 2.5 y for PFBA, 5.0 y for 8:2 FTOH and 7.0 y for 10:2 FTOH. In contrast, declining or non-changing trends, were observed for PFOA and PFOS at Zeppelin (PFOA, half-life, t 1/2  = 7.2 y; PFOS t 1/2  = 67 y), and Andøya (PFOA t 1/2  = 1.9 y; PFOS t 1/2  = 11 y). The differences in air concentrations and in time trends between the three sites may reflect the differences in regional regulations and source regions. We investigate the source region for particle associated compounds using the Lagrangian particle dispersion model FLEXPART. Model results showed that PFOA and PFOS are impacted by air masses originating from the ocean or land. For instance, PFOA at Alert and PFOS at Zeppelin were dominated by oceanic air masses whereas, PFOS at Alert and PFOA at Zeppelin were influenced by air masses transported from land. Graphical abstract: Highlights: First overview of measured concentrations and time trends of PFASs in Arctic air. PFOA, PFOS, PFBA, FTOHs showed increasing trends in air at Alert. Declining or no trends were observed for PFOA and PFOS at Zeppelin and Andøya. PFOA and PFOS are impacted by air from the ocean, or land, depending on the site.